2015
DOI: 10.2298/tsci140703108m
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bioethanol ultrasonic generated aerosols application on diesel engine performances

Abstract: In this paper the effects of an experimental bioethanol fumigation application using an experimental ultrasound device on performance and emissions of a single cylinder diesel engine have been experimentally investigated. Engine performance and pollutant emissions variations were considered for three different types of fuels (biodiesel, biodiesel-bioethanol blend and biodiesel and fumigated bioethanol). Reductions in brake specific fuel consumption and NOx pollutant emissions are correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
0
14
0
1
Order By: Relevance
“…Other operational and injection parameters affecting engine performance are rate of injection, injection pattern, number of injections [1], coolant temperature, working stability level etc. [2], [3], [4], [5].…”
Section: Study Of the Scientific Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Other operational and injection parameters affecting engine performance are rate of injection, injection pattern, number of injections [1], coolant temperature, working stability level etc. [2], [3], [4], [5].…”
Section: Study Of the Scientific Literaturementioning
confidence: 99%
“…Reductions in brake specific fuel consumption and pollutant emissions are correlated with the use of bio-fuel and ultrasonic technology, comparative to use of known fuel blends. Considering the fuel consumption as Diesel engine's main performance parameter, the proposed fuel supply method, offers the possibility to use more efficient renewable biofuels (bioethanol), with immediate effects on environmental protection [5].…”
Section: Our Related Research Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…An optimized performance of the engine can only be obtained with an adequate combination of all three injection parameters. Novel bioethanol fumigation applications for the fuelling of a dual-fuel diesel engine were experimentally investigated [4]. A major average reduction of 31.5% x in the NOx emission together with a slight increase in the engine thermal efficiency was achieved using NB20 in comparison with the use of the B5 blend.…”
Section: Introductionmentioning
confidence: 99%
“…Even if the current solution implies the use of a small quantity of diesel -that anyway represents under 10% of the total amount of fuel supplied to the cylinder -for future solution the diesel fuel could be replaced with renewable solutions like dimethylether, which has been proved by many researchers to be a viable solution for diesel [2][3][4][5]. A survey of the available literature has showed that there are numerous studies about the use of ethanol fumigation [6][7][8][9] and diesel-ethanol blends [10][11][12][13][14][15], but very few studies that cover such a process that involves a separate direct injection of both fuels (diesel and ethanol), in which the diesel pilot injection is used to create the required conditions for the autoignition of a main ethanol injection, which is believed to be due to its higher complexity. The aim of this solution is to reduce the NO x and soot emissions, while taking advantage of the higher efficiency of the Diesel process.…”
Section: Introductionmentioning
confidence: 99%